Climate Smart Agriculture (CSA) Training Guide - Dejene, Sintayehu W.; Terefe, Tadesse; Belay, Berhanu; Amha, Yosef; Demissie, Teferi Dejene (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Agriculture, as the backbone of the Ethiopian economy, contributes roughly 40% of GDP, more than 75% of employment, and 80% of foreign exchange earnings (FAO 2021). Ethiopian agriculture is heavily reliant on natural rainfall, with irrigation used on only about 5% of total cultivated land (USAID 2021). As a result, the sector is highly vulnerable to climate change. Climate change endangers the country's agriculture development, natural resources, biodiversity conservation, and government poverty-reduction efforts. Climate change-related impacts such as food insecurity, malnutrition, poverty, biodiversity loss, and loss of livelihood are deeply intertwined and continue to be the country's primary development challenges. In 2021/2022, climate change has caused Ethiopia to suffer one of its worst droughts that has ravaged vast parts of the country. The drought has ravaged livestock and wildlife resources. Future prediction suggest that Ethiopia will continue to suffer from climate change related problems. Thus action is needed to address problem.